Exploring the effect of menstrual loss and dietary habits on iron deficiency in teenagers: A cross-sectional study - Lisa Söderman; Anna Stubbendorff; Linnea V. Ladfors; Beata Borgström Bolmsjö; Peter Nymberg; Moa Wolff (PLoS ONE, 2025)
Adolescent girls are particularly susceptible to iron deficiency due to increased iron requirements during the pubertal growth spurt, combined with iron loss following menarche. This study aimed to investigate the prevalence of heavy menstrual bleeding in an adolescent population using the SAMANTA questionnaire and to explore its relationship with dietary habits and iron deficiency. This cross-sectional study was conducted in two Swedish high schools in 2023. Post-menarchal female students, aged 15 and older, were included (n = 394). Data were collected on-site through a patient-reported survey, including the SAMANTA questionnaire for heavy menstrual bleeding, and by blood sampling. Meat-restricted diet was analyzed in relation to iron status. Descriptive analysis and regression analysis were used to assess the prevalence of heavy menstrual bleeding and its relationship with dietary habits and iron deficiency, defined as ferritin <15 µg/L. The prevalence of heavy menstrual bleeding and iron deficiency in the cohort was 53% (208/394) and 40% (157/394), respectively. In univariate analysis, heavy menstrual bleeding (OR 3.0, 95% CI [2.0, 4.6]) and a meat-restricted diet (OR 3.5, 95% CI [2.2, 5.6]) were both associated with increased odds of iron deficiency. When assessing the joint effect of having heavy menstrual bleeding and a meat-restricted diet, the odds of iron deficiency were 13.5 times higher compared to omnivore individuals with normal menstruation (OR 13.5, 95% CI [6.4, 28.7]). Overall, the prevalence of iron deficiency in this population of adolescent girls was very high. Heavy menstrual bleeding and a meat-restricted diet were both independently associated with increased odds of iron deficiency. However, odds for iron deficiency were monumentally higher when combining these two variables, thus highlighting the importance of assessing and addressing both excessive output and low intake of iron.